Building Tourism Awareness Areas With Local Wisdom - Andriansyah Andriansyah; Watriningsih Watriningsih; Radja Erland Hamzah; Setya Ambar Pertiwi (PETANDA: Jurnal Ilmu Komunikasi dan Humaniora, 2020)
The purpose of research writing is to provide input on government policies in building tourism-conscious areas based on local wisdom. Indonesia's 70th ranking from 140 countries for tourism and travel competitiveness index. Its position is below Singapore, Malaysia, Thailand. Even though Indonesia has a very beautiful and enchanting wealth of nature and culture, it has even implemented a visa-free visit and an ongoing visit year. The research methodology uses descriptive qualitative methods, with a multidisciplinary approach. The reason, research is done naturally by using various methods, theories, techniques and instruments. As a result, the Tourism Awareness Program was launched since 2003, until now there needs to be an increase towards significant changes and results. The things that need to be improved are, resentment, security and safety and service as well as fostering local and creative industries to build awareness of people who have entrepreneurial characteristics. This research is expected to be used as a Infinity area reference to build a conscious character of community tourism in the destination through local knowledge, and destination in the Indonesian region in general.